Deformation-induced delamination of photovoltaic modules by foaming ethylene-vinyl acetate with supercritical CO2. (May 2022) - Briand, Axel; Leybros, Antoine; Doucet, Olivier; Vite, Marion; Gasmi, Ayoub; Ruiz, Jean Christophe; Lamadie, Fabrice; Grandjean, Agnès
Abstract: Photovoltaic panels are an important source of renewable energy but also represent a growing stock of complex electronic waste. Specific recycling processes are required and this article investigates the potential of supercritical CO2 foaming of the ethylene-vinyl acetate (EVA) in photovoltaic modules as a means of safely taking them apart, layer by layer. The effects of the CO2 temperature, pressure and depressurization rate on the deformation of EVA layers were characterized using in-situ measurements of area expansion and curvature during the foaming process. Peel tests were performed on treated and untreated samples to quantify the loss of adhesion at the different EVA interfaces. The data show that with the temperature set above the melting point and an initial pressure of at least 150 bar, the deformation of the EVA layers can be increased by increasing the depressurization rate. The correlation between the percentage loss of adhesion and area expansion of the EVA layers shows that the mechanical stress induced by deformation is an important factor in the delamination process. Moreover, the amount of separation achieved and the optimal combination operating parameters depend on the nature and morphology of the neighbouring layer. This process properly separates each PV module layer (glass, cell and backsheet) from EVA for their specific recycling. These results are an important first step in the development of an efficient recycling process for photovoltaic modules and other types of layered electronic devices. Graphical Abstract: ga1